Physical child abuse and causative factors in Edirne, Turkey - Şahin, Erkan Melih; Yetim, Dilek (The Turkish Journal of Pediatrics, 2011)
The aim of this study was to identify the frequency and causative factors of physical child abuse and any correlations with other domestic violence types. In a representative sample of 15-49-year-old married women living in Edirne chosen with stratified cluster sampling, 275 women were interviewed face-to-face in their residence or places of employment. The questionnaire used included any violent behavior of the women or their husbands toward their children as well as demographic features, habits, Marriage Relation Scales, Multidimensional Scale of Perceived Social Support, history of partner abuse, and childhood violence exposition. The physical child abuse rate was 61.1% among the women and 20.7% among the husbands according to the women's declarations. Social support was not associated with child abuse rates. Child abuse rate among the women was increased 2.7 times in the presence of the partner's child abuse, 1.6 times with each additional child, 3.1 times in the presence of a history of physical childhood abuse, and 1.9 times in the presence of a history of partner abuse. Child abuse by the husbands was increased 2.9 times in the presence of physical childhood abuse history and 2.3 times in case of partner abuse. Child abuse is widely seen although morally unacceptable in contemporary society. Violent behaviors spread out horizontally among family members and vertically through generations, although at decreasing rates. Healthcare professionals should behave in a sensitive manner and take responsibility together with those from other related fields to prevent this condition, which can result in several social complications.